2013
DOI: 10.1186/ar4182
|View full text |Cite
|
Sign up to set email alerts
|

Canonical Wnt signaling and caveolae play a role in intervertebral disc degeneration; the continuing saga of the mysterious notochordal cell

Abstract: Over the past few decades small animal models mainly involving rodents and rabbits have been developed whereby needle puncture, stab incision or enzymatic approaches have been validated to create the degenerative disc. Although important, these models continue to be plagued by biological attributes that limit applicability to the human condition. However, the fascinating story of two naturally occurring subspecies of canine, the non-chondrodystrophic and chondrodystrophic canine, provides us with an animal mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
(11 reference statements)
1
4
0
Order By: Relevance
“…Subgroup analysis of the three different degeneration degrees showed that axin2 gene expression was significantly higher in chondrodystrophic dogs compared with non-chondrodystrophic dogs. Their findings showed that at the early stage of disc degeneration in dogs, the number of notochord cells decreased, and the number of chondrocyte-like cells increased, along with reduced expression of Wnt/β-catenin, which was consistent with the results of the present and previous studies 45 46 . However, some studies reported that compared with healthy controls, Wnt/β-catenin pathway activity in a degenerated intervertebral disc was up-regulated 48 49 50 .…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Subgroup analysis of the three different degeneration degrees showed that axin2 gene expression was significantly higher in chondrodystrophic dogs compared with non-chondrodystrophic dogs. Their findings showed that at the early stage of disc degeneration in dogs, the number of notochord cells decreased, and the number of chondrocyte-like cells increased, along with reduced expression of Wnt/β-catenin, which was consistent with the results of the present and previous studies 45 46 . However, some studies reported that compared with healthy controls, Wnt/β-catenin pathway activity in a degenerated intervertebral disc was up-regulated 48 49 50 .…”
Section: Discussionsupporting
confidence: 89%
“…Although early processes in disc degeneration have been investigated in histopathology, the biomolecular signal transduction pathways involved in the conversion of notochord cells into chondrocyte-like cells remain unclear 43 44 . Among the many signalling pathways, the Wnt/β-catenin pathway plays an important regulatory role in disc embryonic development and has become a hot spot in disc degeneration in recent years 20 45 46 . Smolders and his colleagues used Dual channel DNA microarrays to compare healthy NP containing only notochord cells (notochord cells-rich), NP with a mixed population of notochord cells and chondrocyte-like cells (Mixed) and NP containing solely chondrocyte-like cells (chondrocyte-like cells-rich) in both non-chondrodystrophic and chondrodystrophic dogs 47 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in a previous study, hyperbaric oxygen treatment suppresses the MAPK signaling pathway in degenerated human intervertebral disc cells ( 41 ). In addition, investigators from The Netherlands have used a canine model of IDD to examine the biochemical changes associated with chondroid metaplasia, and found a downreguation of Wnt signaling and caveolin-1 expression ( 42 ). Our results suggest that miRNAs are important regulators of IDD through the modulation of several signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Various messengers that act from within the cell to initiate a variety of signaling evens have been identified . Several research groups have also suggested that Wnt signaling plays an important role in IVD degeneration . Furthermore, we have reported the relationship between Tumor Necrosis Factor‐α (TNF‐α) and Wnt signaling in IVD cells .…”
mentioning
confidence: 95%